2017
DOI: 10.1590/0104-4060.51048
|View full text |Cite
|
Sign up to set email alerts
|

Políticas de educação bilíngue para estudantes surdos: contribuições ao letramento acadêmico no ensino superior

Abstract: RESUMOO ingresso progressivo de estudantes surdos ao ensino superior, na última década, demandou mudanças institucionais importantes quanto ao direito à educação bilíngue, ou seja, oportunizar acesso e produção de conhecimento em Língua Brasileira de Sinais (Libras) e em Língua Portuguesa na modalidade escrita. Nesse sentido, este artigo tem como objetivo discutir o processo de educação bilíngue de estudantes surdos no ensino superior, apresentando ações desenvolvidas no âmbito da Universidade Federal do Paran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
0
2
0
11
Order By: Relevance
“…In the SciELO platform, 39 published studies were found with themes related to accessibility and/or inclusion in higher education. Within this theme, the studies focused on different specificities: teacher training to attend students with disabilities in higher education (Reis, Eufrásio and Bazon, 2010); the right to inclusion in higher education (Araujo, 2017); inclusion specifically of students with visual disabilities (Fernandes and Costa, 2015;Regiani and Mól, 2013); inclusion and accessibility specifically of students with hearing disabilities (Bisol et al, 2010;Fernandes and Moreira, 2017;Martins and Napolitano, 2017;Mesquita, 2018); inclusion in higher education (Almeida and Ernica, 2015;Calheiros and Fumes, 2016;Facci, Silva and Souza, 2018;Nozu, Bruno and Cabral, 2018;Oliveira, Gonçalvez and Oliveira, 2016;Poker, Valentim and Garla, 2018); normalization, access legitimacy, participation, and formation (Cabral and Melo, 2017); accessibility in higher education (Silva and Ferreira, 2017); permanence of students with disabilities (Maciel and Anache, 2017); admission and permanence (Castro and Almeida, 2014;Moreira, Bolsanello and Seger, 2011); accessibility and permeance (Garcia, Bacarin and Leonardo, 2018); centers of accessibility in the universities (Ciantelli andLeite, 2016;Ciantelli, Leite and Nuernberg, 2017;Melo and Araújo, 2018); attention to diversity in higher education (Martos-García and Valencia-Peris, 2016); mapping of students in special education (Lourenço and Battistella, 2018); survey on the number of PWD enrolled in higher education (Duarte et al, 2013); participation of students with disabilities in higher education (Gesser and Nuernberg, 2017); meanings of inclusion through students' perspectives (Almeida and Ferreira, 2018); satisfaction evaluation of students with disabilities (Guerreiro, Almeida and Silva Filho, 2014;...…”
Section: Introductionmentioning
confidence: 99%
“…In the SciELO platform, 39 published studies were found with themes related to accessibility and/or inclusion in higher education. Within this theme, the studies focused on different specificities: teacher training to attend students with disabilities in higher education (Reis, Eufrásio and Bazon, 2010); the right to inclusion in higher education (Araujo, 2017); inclusion specifically of students with visual disabilities (Fernandes and Costa, 2015;Regiani and Mól, 2013); inclusion and accessibility specifically of students with hearing disabilities (Bisol et al, 2010;Fernandes and Moreira, 2017;Martins and Napolitano, 2017;Mesquita, 2018); inclusion in higher education (Almeida and Ernica, 2015;Calheiros and Fumes, 2016;Facci, Silva and Souza, 2018;Nozu, Bruno and Cabral, 2018;Oliveira, Gonçalvez and Oliveira, 2016;Poker, Valentim and Garla, 2018); normalization, access legitimacy, participation, and formation (Cabral and Melo, 2017); accessibility in higher education (Silva and Ferreira, 2017); permanence of students with disabilities (Maciel and Anache, 2017); admission and permanence (Castro and Almeida, 2014;Moreira, Bolsanello and Seger, 2011); accessibility and permeance (Garcia, Bacarin and Leonardo, 2018); centers of accessibility in the universities (Ciantelli andLeite, 2016;Ciantelli, Leite and Nuernberg, 2017;Melo and Araújo, 2018); attention to diversity in higher education (Martos-García and Valencia-Peris, 2016); mapping of students in special education (Lourenço and Battistella, 2018); survey on the number of PWD enrolled in higher education (Duarte et al, 2013); participation of students with disabilities in higher education (Gesser and Nuernberg, 2017); meanings of inclusion through students' perspectives (Almeida and Ferreira, 2018); satisfaction evaluation of students with disabilities (Guerreiro, Almeida and Silva Filho, 2014;...…”
Section: Introductionmentioning
confidence: 99%
“…The differentiated correction of written exams in Portuguese by deaf people who are fluent in Libras is not a new topic, on the contrary, it is the subject of old demands of the deaf community (Brito, 2010;Feneis, 2011;Fernandes & Moreira, 2017). The defense based on the linguistic form of writing the exams, that is, with questions written in clearer terms and with an intelligible lexicon to this audience is available.…”
Section: Discussionmentioning
confidence: 99%
“…Esclarecem Ansay e Moreira (2020) que, no Brasil e no Chile, embora exista um arcabouço legal em defesa dos direitos dos alunos deficientes, há carência de efetividade e a preponderância é de obstáculos ao acesso ao Ensino Superior por pessoas cegas, surdas e com limitações mental ou motora. Para superar barreiras, especialmente pelos estudantes surdos, solicita-se a interação de todos os integrantes da comunidade acadêmica, não somente aluno e tradutor-intérprete (Fernandes;Moreira, 2017).…”
Section: Coocorrência De Palavras-chave E Principais Categorias Temát...unclassified
“…Em referência às políticas direcionadas para o Ensino Superior, a depender dos objetivos grafados e dos resultados logrados, vigilantes, os estudos brasileiros difundem ponderações críticas (Canen;Oliveira, 2000;Libâneo;2016;Redin, 2017;Saviani, 2020) ou elogiosas (Francis-Tan; Tannuri-Pianto; 2018), relacionando-as à conjuntura política do país, além de recomendarem aprofundamento investigativo Soares, 2018) e estratégias contributivas para o alcance da efetividade social (Fernandes;Moreira, 2017;Queiroga et al, 2021;Salvador et al, 2022).…”
unclassified